Black Cat. Vol. 08, Cerberus strikes - Yabuki, Kentaro (Viz Media, 2007)
Train Heartnet, also known as Black Cat, was an infamous assassin for a secret organization called Chronos until he abandoned that cold blooded existence to live on his own terms as an easygoing bounty hunter. But is his past as far behind him as he thinks?